Sorotan Literatur Kajian Penentuan Liabiliti Pembekal Dan Pesakit Dalam Rawatan Bekam Dari Perspektif Syariah Dan Undang-Undang - Nurul Izzah Syafiqah Osman; Abd Hamid Abd Murad; Ahmad Syukran Baharuddin (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2024)
The practice of traditional medicine has been in existence since time memorial and also one of the practices which had been practiced by our Prophet (p.b.u.h.). Various writings have been done related to cupping from the religious point of view. Meanwhile, there are various writings on the legal aspects of the treatment of traditional medicine in developed countries such as The United States of America, United Kingdom, and Australia. Still, there is no extensive study on the legal aspects of traditional medicine treatment in Malaysia,especially on cupping from the Syariah and legal perspective. This literature review analyses the critical literature related to the study of determining the provider’s liability in cupping treatment. This article used the library method and textual documents. This study found a gap in the determination of liability and the existence of such guidelines will protect the service providers of cupping if any negligence or incidents happen during the cupping treatment. This paper suggests that further research will be done to refine this matter. It is essential to all practitioners and patients receiving cupping therapy, whether in Syariah and legal perspective.